Pengaruh Gaya Kepemimpinan Transformasional, Budaya Organisasi dan Lingkungan Kerja Terhadap Kinerja Karyawan pada PT. PLN (Persero) Rayon Puruk Cahu - Gemarifannoor Gemarifannoor; Hairudinor Hairudinor; Hasanur Arifin (Universitas Lambung Mangkurat, 2018)
The implementation of transformational leadership, organizational culture and the influence of the working environment has not been carried out measurements both quantitatively and qualitativelyat the PT. PLN (Persero) Rayon Puruk Cahu.This study aims to identify and analyze the effect of transformational leadership style, organizational culture and work environment to employees performance at PT. PLN (Persero) Rayon Puruk Cahu simultaneously or partially.These samples included 67 respondents who were determined by sampling saturated. Data were collected by questionnaire and then the results were analyzed using multiple linear regression analysis.The results showed that (1) Partially, transformational leadership variable (X1) shows sig 0.812. Because sig> 0,05, then variable of transformational leadership style have not significant effect to employee performance variable of PT. PLN (Persero) Rayon PurukCahu. (2) Partially, organizational culture variable (X2) shows sig 0,000. Because sig <0,05, hence organizational culture variable significantly influence to employee performance of PT. PLN (Persero) Rayon Puruk Cahu. With the value of t arithmetic of 4.357 which this value is greater than the value of t arithmetic other variables, then the organizational culture variables become the most influential variable affecting the performance performance of employees of PT. PLN (Persero) Rayon Puruk Cahu. (3) Partially, the working environment variable (X3) shows sig 0.041. Because sig <0,05, then work environment variable significantly influence to employee performance of PT. PLN (Persero) Rayon Puruk Cahu. (4) Simultaneously or together, transformational leadership style variables, organizational culture, and work environment in which the F test results show sig 0,000, since sig <0.05, the variables of transformational leadership style, organizational culture, and work environment significantly influence On the performance of employees of PT. PLN (Persero) Rayon Puruk Cahu. Keywords: Transformational Leadership Style, Organizational Culture, Work Environment, Performance